2019
DOI: 10.1108/ilt-09-2018-0356
|View full text |Cite
|
Sign up to set email alerts
|

Influence of tribofilms on failures and friction of gears with particular focus on running-in

Abstract: Purpose This paper aims to address the influence of tribofilms and running-in on failures and friction of gears. The operation regime of gears is increasingly shifted to mixed and boundary lubrication, where high local pressures and temperatures occur at solid interactions in the gear contact. This results in strong tribofilm formation due to interactions of lubricant and its additives with the gear flanks and is related to changes of surface topography especially pronounced during running-in. Design/methodo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…Figure 2 shows the mechanical layout of the considered test rig in back-to-back configuration with a center distance of 91.5 mm. Only the main features of the test rig are described based on the description and wording of Lohner et al (2017), Yilmaz et al (2019) and Ziegltrum et al (2017, 2019). For more details, the reader may be referred to Hinterstoißer(2014) and Lohner (2016).…”
Section: Methodsmentioning
confidence: 99%
“…Figure 2 shows the mechanical layout of the considered test rig in back-to-back configuration with a center distance of 91.5 mm. Only the main features of the test rig are described based on the description and wording of Lohner et al (2017), Yilmaz et al (2019) and Ziegltrum et al (2017, 2019). For more details, the reader may be referred to Hinterstoißer(2014) and Lohner (2016).…”
Section: Methodsmentioning
confidence: 99%
“…While lubricant has a major impact on reducing running-in time, careful selection is needed to achieve the best results for the running-in method. The impact of running-in and tribofilms on gear failures and friction was studied by Ziegltrum et al [12], and the results revealed that during running-in, tribofilm production can be more important than surface roughness change in terms of gear failures and friction. The central film thickness for electrohydro-dynamic lubrication was investigated by Dowson et al [13] and showed for the first time full numerical film thickness and pressure distributions and a curve fitted minimum film prediction.…”
Section: Introductionmentioning
confidence: 99%
“…Friction and wear of rolling contacts are influenced by boundary layers, which prevent direct metallic contact. The characteristics of these boundary layers depend mainly on the finishing process and the wear in of the contact partners (Brecher et al, 2017;Ziegltrum et al, 2017;Brinksmeier, 1982;Mach, 2003;Schulz, 2009;Berlet et al, 2010). In the conventional production of gears, the tooth flanks of the gears are ground in the final manufacturing process step.…”
mentioning
confidence: 99%